Legal aspect of Governing Electronic Transport Document in Indonesian Port - Irma Rachmawati Maruf; Putrì Mety Zalinda; Maman Budiman; Tuti Rastuti; Yogi Yogaswara; Dzulfiqar Rizqan Agistra (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
This paper aims to discover an appropriate port management model so that Indonesian ports can export technology while also supporting managerial and functionally international trade.   The blockchain chain model can help Indonesian ports compete with ports in neighboring countries.   The study also explores whether managing shipping workflows and documents can adopt the Blockchain of existing maritime ports. This study employs qualitative research methods.   The research used secondary data from international regulations and conventions while supporting information with depth interview data; Current studies build a conceptual framework through a systematic project review conducted in conjunction with scientific literature published in journals and conference processes, random sampling, and observation over the past decade. The results showed that the project under review could be compiled into three main conceptual areas: document workflow management, financial processes, and device connectivity. However, having a clear linkage, no project under review considered all three places at once. Concepts related to maritime document workflows receive broad support among the projects under consideration. In addition, the project under review inadvertently followed similar goals set out in the port management scientific project before the introduction of blockchain technology.